THE OMNISCIENT NARRATOR IN HAWTHORNE’S SIGHTS FROM A STEEPLE - Widodo, Herditya Wahyu (J-ELLiT (Journal of English Language, Literature, and Teaching), 2021)
The study of Nathaniel Hawthorne’s authorial style has been an intriguing one, and many studies have tried to examine his style that more or less set the path of American Literature. In this study, I intend to further such studies and explain how Hawthorne’s omniscient observations as the narrator in his earlier short story, Sights from A Steeple, can actually be related, and is applied, to his other, later short stories and works. In the process of doing so, I intend to explain the defining style that Hawthorne follows in most of his short stories. The narrator in Sights from A Steeple, seen acting as the author himself, has an unusually superior power of observation, using to give judgments and insights into the characters and events. These characters, events, and insights are then developed into similar but more detailed characters and significant events in Hawthorne’s short stories: Wakefield, My Kinsman, Major Molyneux, Rappacini’s Daughter and  Artist of the Beautiful. In this way, Sights from A Steeple acts like snapshots of Hawthorne’s other short stories.